2015
DOI: 10.1128/aac.03708-14
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an In Vitro Pharmacokinetic/Pharmacodynamic Model To Test the Antibacterial Efficacy of Antibiotic Polymer Conjugates

Abstract: bThis study describes the use of a novel, two-compartment, static dialysis bag model to study the release, diffusion, and antibacterial activity of a novel, bioresponsive dextrin-colistin polymer conjugate against multidrug resistant (MDR) wild-type Acinetobacter baumannii. In this model, colistin sulfate, at its MIC, produced a rapid and extensive drop in viable bacterial counts (<2 log 10 CFU/ml at 4 h); however, a marked recovery was observed thereafter, with regrowth equivalent to that of control by 48 h. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…in inflammatory regions an enhanced permeability of the blood vessel wall was observed; therefore, the application of polymersomes as nanotransporters is also for the treatment of infections very promising. 25 Apart from the EPR effect, the size of polymersomes affects their fate in vivo in a variety of ways. Based on the assumption of intravenous injection as common practice in cancer therapy, nanotransporters will become in contact with serum proteins, and an opsonization will occur immediately.…”
Section: ■ Introductionmentioning
confidence: 99%
“…in inflammatory regions an enhanced permeability of the blood vessel wall was observed; therefore, the application of polymersomes as nanotransporters is also for the treatment of infections very promising. 25 Apart from the EPR effect, the size of polymersomes affects their fate in vivo in a variety of ways. Based on the assumption of intravenous injection as common practice in cancer therapy, nanotransporters will become in contact with serum proteins, and an opsonization will occur immediately.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The World Health Organization has identified antimicrobial resistance as one of the most important problems that affects human health 2. Although there has been modest success in the development of new drugs against Gram‐positive bacteria, the therapeutic options for Gram‐negative species are extremely limited 3. 4 Furthermore, there are very few drugs for Gram‐negative species in the development pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer therapy, passive targeting relies on the enhanced permeability and retention (EPR) effect of tumors, an effect of their unique physiology and metabolic rates. Existing evidences showed that EPR effect is not only present in tumors, but also exists in bacterial infections . Indeed, it has been shown that diffusion of therapeutic‐NPs into biofilm was highly depended on PCPs of NPs (e.g., size and surface charge), demonstrating EPR effect in biofilm drug delivery.…”
Section: Mesoporous Silica Nanostructuresmentioning
confidence: 99%